Management of teeth discoloration with external bleaching treatment: a case report: Penatalaksanaan diskolorasi gigi dengan perawatan bleaching eksternal: laporan kasus - Aries Chandra Trilaksana; Febrianty Alexes Siampa (Makassar Dental Journal PDGI Makassar, 2022)
The objective of this article is management of teeth discoloration with external bleaching used bleaching agent hydrogen pe-roxide (H2O2) 40% on a 28-year-old woman came to the Hasanuddin University RSGMP with complaints of yellowish teeth. The patient wants her teeth looks brighter. In-office bleaching procedure was performed by initial color determination score 8 with opalescence boost shade guide. Dental optragate was placed in the patient’s mouth, cleanedthe surface of the teeth with a brush and pumice, application of astringent, gingival barrier in upper and lower teeth. Application of 40% H2O2 bleaching agent for20 minutes then cleaned, desensitizing agent application, and final color adjustment. This research results a significant color change from score 8 to 2 using opalescence boost shade guide and concludes that treatment of teeth discoloration using 40% H2O2 provides significant teeth color changes in a short time and considered as an effective method.